A Covert Standardized Patient With Medication-Induced QT Prolongation - Kelly Karpa; Kristen Grine (Association of American Medical Colleges, 2015)
Abstract Introduction This is a covert simulation scenario that was implemented during a family medicine clerkship for third-year medical students at our regional medical school campus. It was developed to assess students' competency with identifying adverse drug reactions, medication planning/management, and patient education about medications. Methods Given the covert nature of this encounter in a working clinic, students did not know in advance that the patient in the examination room was a standardized patient. Not only was students' pharmacology knowledge tested in real time but also their clinical skills and their ability to research information quickly, synthesize, treat, and present to their attending. This covert standardized patient situation allows an attending physician to assess simultaneously students' knowledge, communication skills, ability to research information efficiently during a visit, clinical treatment abilities, and note-writing aptitude. Results This activity was implemented with 23 third-year medical students during their family and community medicine clerkship. It may also be an appropriate activity for an interprofessional team of student learners or for residents. Overall, we found that most students were able to identify the chief complaint as a medication-related issue (drug-induced QT syndrome). However, students did not generally identify all the underlying medication issues (there were multiple medication-related problems built into the case). Of the problems they did identify, students usually were able to correctly suggest a plan to correct the issues. Discussion These findings suggest that students (and ultimately patients) may benefit if students are provided with additional opportunities to practice their medication counseling/education skills with patients.